The formation of Rhizobium cicer in pea - Khamdamova Elnura; Isokova Ezazkhan; Suvonova Gozal; Mavlonov Bakhodir (BIO Web of Conferences)
The article analyzes the effect of different planting scheme and the effect of inoculants on the mass of nodules in the roots of pea varieties in the conditions of irrigated meadow-gray soils of Samarkand region. Umid variety produces more buds than Yulduz and Zumrad varieties. In all three cultivars, as the feeding area of the plants expands and Planteco Nut MC285 inoculant is applied, numerous root nodules form. The mass of nodules formed in the roots of pea varieties differed by variety, and the mass of nodules was higher in the Umid variety than in other varieties. As the nutritional area of plants expanded, that is, as the thickness of the stem decreased, the mass of nodules increased, especially when the drug Rizolain was used, the mass of nodules in the roots of Pea varieties was ensured.